Usefulness of ultra-sensitive troponin to predict anthracyclines and trastuzumab related cardiac dysfunction. (3rd October 2022) - Del Castillo, S; Llamedo, C; Capdeville, S; Fileni, L; Scarponi, C; Belziti, C; Rossi, E; Falconi, M; Perez De Arenaza, D; Pizarro, R
Abstract: Background: Cancer therapeutics–related cardiac dysfunction usually known as cardiotoxicity (CTX) is a common adverse effect of anthracyclines and anti-Her2 agents. In recent years, evidence of usefulness of ultrasensitive troponin for early diagnosis of CTX has increased, however the cut-off values of this biomarker remain uncertain. Purpose: To assess the usefulness of ultrasensitive troponin T (UsTnT) to identify patients at risk of developing CTX and determine cut-off values for this biomarker. Methods: Patients with diagnosis of solid or hematologic malignancies scheduled to receive therapy including anthracyclines and/or trastuzumab were prospectively included. Echocardiogram was performed prior to chemotherapy, and repeated 3 and 6 months later. UsTnT was measured at baseline and 3 months after starting chemotherapy and the increase of this biomarker from baseline was calculated. This UsTnT has a range of 3–10, 000 pg/mL with a 99th percentile <15 pg/mL. Receiver operating characteristic curve was used to find out the best cut-off values followed by a multivariate analysis. The primary endpoint was the presence of CTX defined as a decline of left ventricular ejection fraction (LVEF) ≥10% at 6 months from baseline. Results: A total of 141 patients were included (mean age 56±15 years, 85, 8% were women, the most frequent diagnosis being breast cancer: 61.7%). Thirty-three patients (23.4%) met criteria of the primary endpoint of CTX. Patients with CTX showed significantly higher values of UsTnT at 3 months (18.2±14, 9 vs 11.8±10, 7 pg/mL, p=0.008) and also showed a higher increase of UsTnT from baseline (11.8±12.8 vs 5±8.2 pg/ml, p<0.001) (figure 1). The value of UsTnT at 3 months ≥13 pg/mL and an increase of UsTnT from baseline ≥14 pg/mL were selected as the best cut-off values. Figure 2 resumes sensitivity, specificity and predictive values. Those patients who had UsTnT at 3 months ≥13 pg/mL had a 3.8 fold increased risk of developing CTX in a multivariate analysis adjusted by age and left ventricular hypertrophy (OR: 3.8 [95% CI: 1.6–9.3], p=0.003) while an increase of UsTnT from baseline ≥14 pg/mL showed almost 12 fold increased risk for the primary endpoint in the same model (OR: 11.95 [95% CI: 3.9–36.6], p<0.001). Conclusions: UsTnT is a good biomarker for detecting early myocardial injury which allows the identification of patients at risk for developing CTX with only two measurements during cancer treatment. Funding Acknowledgement: Type of funding sources: None.